Quality Management in Health Care System in Bangladesh (Global Journal of Management and Business Research, 2017)
Healthcare and quality are inseparable items and therefore giving services in a sector like healthcare without quality is not expected at all In Bangladesh healthcare is provided principally through hospitals run by government or through private clinics with a small proportion delivered by NGOs But the main problem is that the total system of health care services both in public and private sectors are not up-to- date genuinely and again the quantity of the doctors are less than expectation To overcome this huge problem redesigning of existing health care system or setting up an influential service plan is a must issue for Bangladesh Firstly the concentration in this project will be to discuss the basic problems and analyze them effectively After that the follow up will be to find out the most prominent issues both in manpower and management sector according to voice of patient and voice of employee Lastly with the basis of limited resources in Bangladesh Two methods will be set up both in manpower and management which are very much feasible to implement in our health care sector The ultimate target and research of ours are to create an effective communication or service system between doctors and patients with assuring high level of quality
Keywords: survey; system analysis; redesign; talent management; 5S